What Jane Austen Read (in the Hampshire Chronicle) - Franta, Andrew (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2010)
This essay considers the Hampshire Chronicle, and the provincial newspaper in general, as a context for reading Austen. If the provincial newspaper would appear to afford a sharper framework for the historical interpretation of Austen’s novels, the Hampshire Chronicle and the history of the provincial press instead raise larger questions about the constitution of ‘the local’ in the early nineteenth century and suggest a different basis for understanding the significance of Austen’s focus on everyday life.